Follicular variant of peripheral T-cell lymphoma - Archana Lakshmanan; S Annapurneswari; Sheila Nair (Wolters Kluwer Medknow Publications, 2017)
Globally, peripheral T-cell lymphomas (PTCLs) constitute about 12% of all non-Hodgkin lymphomas, of which the unspecified category is the most common subtype (30%). Mostly, the unspecified category shows a diffuse pattern of involvement in the lymph nodes. However, rarely, they may show a follicular/nodular pattern mimicking a follicular lymphoma. We report a case of a follicular variant of PTCL, not otherwise specified. This case displayed a striking nodular/follicular pattern with an admixture of small (centrocyte-like) and large (centroblast-like) cells, thus mimicking a follicular lymphoma. The neoplastic cells were strongly positive for both CD3 and CD20. In addition, they were positive for pan T-cell markers and PD-1. T-cell receptor gene rearrangement studies highlighted a monoclonal T-cell population. Even though this variant of PTCL is very rare, it is important to keep it as a differential for the lymphomas exhibiting nodular pattern.